Pengembangan Manajemen Bisnis dan Diversifikasi Produk untuk Meningkatkan Daya Saing (Studi Kasus pada Mayesty Cake & Cookies): Penelitian - Andry Mochamad Ramdan; Yanti Purwanti; Indah Putri Cahya; Revansyell Syahla (Lembaga Penelitian dan Pengabdian Masyarakat, 2025)
Micro, Small, and Medium Enterprises (MSMEs) are fundamental pillars of the Indonesian economy, but face significant challenges in terms of management, legality, and technology adaptation. This study aims to improve the competitiveness of MSME Mayesty Cake & Cookies in West Bandung Regency through a structured mentoring program. The main problems identified in partners are (1) limited understanding of product diversification and quality, (2) the absence of structured business management, especially in the ordering flow and financial recording, (3) the absence of business legality, and (4) the use of digital marketing that is not optimal. The implementation method used is Participatory Action Research (PAR), which involves active participation of partners in every stage, starting from situation analysis, training, technical guidance, facilitation, to mentoring. The results of this program show significant improvements: (1) partners successfully obtained a Business Identification Number (NIB) which is the legal foundation of the business, (2) there was an improvement in business management with the implementation of a standard ordering flow and digital financial recording through the BukuWarung application, (3) a new packaging design was produced that was more informative and attractive, and (4) increased knowledge and initial implementation of digital marketing.